Training on Educational Blog Design and Management for Educators at SMP Rahmat Islamiyah Medan - Hasrian Rudi Setiawan; Muhammad Syukri Maulana (Yayasan Rahmat Islamiyah, 2026)
This community service activity aimed to improve educators’ digital competence through training on educational blog design and management at SMP Rahmat Islamiyah Medan. The rapid development of information technology requires teachers to utilize digital media as innovative, interactive, and accessible learning tools for students. However, some educators still have limitations in designing and managing educational blogs as learning media and platforms for disseminating school information. The program was implemented through observation, material presentation, demonstrations, direct practice, and evaluation stages. The training materials included blog creation, educational content management, blog interface design, and the utilization of blogs as digital learning media. The results of the activity showed improvements in participants’ understanding and skills in independently creating and managing educational blogs. In addition, participants became more creative and confident in utilizing digital technology to support the learning process. Through this training activity, it is expected that the quality of technology-based learning at SMP Rahmat Islamiyah Medan will continue to improve sustainably.